Penerapan Pembelajaran Daring pada Kompetensi Dasar Pembuatan Bolero/Rompi Siswa Kelas XI Tata Busana 1 di SMK Negeri 8 Surabaya - Shinta Amellia Vebri Zhaputri; Lutfiyah Hidayati; Imami Arum Tri Rahayu; Peppy Mayasari (Pusat riset dan Inovasi Nasional, 2024)
The advancement of information and communication technology today can influence the development of education, one of which is through online learning. Online learning can be utilized by teachers and students anytime and anywhere. This research aims to describe: 1) the feasibility of implementing online learning using Google Classroom, Google Meet, and WhatsApp Group on the Basic Competencies of Making Bolero/Vest for 11th-grade students in Fashion Design 1 class at State Vocational High School 8 Surabaya, and 2) students' learning outcomes through the implementation of online learning. This research is descriptive in nature and was conducted at State Vocational High School 8 Surabaya in the Fashion Design 1 class, focusing on the subject of custom-made fashion garment production, specifically the competence of making bolero/vest, during September - October of the 2020/2021 academic year. The number of respondents was 35 students. Data collection methods included observation and assessment of bolero/vest products. The research instruments used were observation sheets and product assessment rubrics. Data analysis was conducted descriptively by calculating the average observation results and categorizing values between complete and incomplete. The research results indicate: 1) the feasibility of learning conducted over 4 meetings shows that the WhatsApp Group application was used during the opening of the lesson, Google Classroom was used in the opening and core learning activities, and Google Meet was used in the core and closing parts. The observation results of the feasibility of learning with the application of Google Classroom, Google Meet, and WhatsApp Group on the basic competencies of making bolero/vest for 11th-grade students in Fashion Design 1 class at State Vocational High School 8 Surabaya are categorized as very good, with an average score of 84, and 2) the learning outcomes of students, where 28 students were declared complete and 7 students were declared incomplete. The classical learning completeness level reached 80%, exceeding the school's KKM (Minimum Mastery Criteria) standard of >76%.